Pemanfaatan Bahan Limbah dari Kaleng Menjadi Sebuah Rak Pulpen - Pakpahan, Enni Halimatussa'diyah; Azri, Riza Nazila; Hakim, Muhammad Wildan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The popularity of canned drinks has sparked the idea of making metal crafts from recycled cans. Usually, canned trash is used to make pen holders or other containers without prior processing. However, recycled cans can also be used to create pressed metal art. This study uses this information to identify the types of cans that can be used as components in metal works produced using pressing techniques, the manufacturing process, and the results of experiments conducted to transform used cans into metal works using pressing techniques. Observation, interviews, and documentation are used to obtain data. The findings show that the best material for metal work produced with pressing techniques is lightweight beverage cans (Tebs packaging and the like). The metal in such cans is only 0.3 mm thick, which is relatively thin, flexible, and suitable for the pressing method. This can make marks with just a few presses. The metal is very easy to shape, which saves time. The process of making used cans starts with washing them, followed by cutting them into rectangular shapes, making patterns, sticking them, tracing them with a pencil or old pen, shaping them according to the design, and finishing.